Storming the world stage the story of Lashkar-e-Taiba - Tankel, Stephen (Hurst & Company, 2011)
On the night of 21 November 2008 Lashkar-e-Taiba gunmen killed more than 170 people and injured over 300 in Mumbai, India's commercial capital. This title charts Lashkar's development from a small group unable to make a dent in the Afghan jihad against the Soviets to the most feared organization in Kashmir and a powerhouse in Pakistani society.